Multicellular Features of Phytoplankton - Abada, Adi; Segev, Einat (Frontiers in Marine Science, 2018)
Phytoplankton are microscopic photosynthesizing organisms that live in the sunlit layer of the ocean. They are of global importance, accounting for half of the primary productivity on Earth. Members of this group can undergo a programmed cell death process that has the hallmarks of apoptosis. The existence of apoptosis-like processes in phytoplankton raises the enigma of why single-celled organisms commit "suicide". Through our own work, and through interpretation of existing literature, we provide evidence suggesting that coccolithophores and diatoms, two key groups of phytoplankton, exhibit a multicellular-like state. These communities regularly aggregate, communicate and execute coordinated behaviors, which are traits that adhere to the core definition of multicellularity. If phytoplankton populations indeed exist in a multicellular-like organization, the benefits of apoptotic processes in phytoplankton could be studied in analogy to multicellular organisms. Given the central role of phytoplankton in many global scale processes, it is fascinating to think how these cells regularly exist in units of physically attached cells that potentially act semi-coherently across kilometer scale. In the bacterial world, our recognition of biofilms as multicellular arrangements furthered the study of bacterial communication and ecology. Similarly, we propose areas of research that would benefit from acknowledging the multicellular traits of phytoplankton. As our oceans become warmer, more stratified and more acidic, key communities of primary-producers are forced to rapidly adjust. Therefore, studying phytoplankton in a multicellular context would be significant in gaining a comprehensive view of phytoplankton physiology and ecology under changing conditions.